An Advanced Qualitative Model Regarding the Role of Oxygen During POCl3 Diffusion in Silicon. Issue 9 (4th August 2017) - Li, Hongzhao; Ma, Fa‐Jun; Hameiri, Ziv; Wenham, Stuart; Abbott, Malcolm
Abstract : POCl3 diffusion has seen decades of research interest and industrial applications. However, further understanding is required for the correlation between the increasing oxygen flow and decreasing inactive phosphorus concentration. In this study, we consider a "free phosphorus oxidation" reaction for a consistent explanation of results in the literature. For verification, four phosphorus doping profiles are fabricated with different oxygen flows during pre‐deposition and drive‐in. Secondary ion mass spectrometry and X‐ray photoelectron spectroscopy are performed on these profiles, with a particular attention to the relative concentrations within the phosphosilicate glass. From experimental results, we not only confirm this reaction, but also present an advanced qualitative model to unlock the fundamental mechanisms during POCl3 diffusion. Abstract : By characterising four phosphorus doping profiles using secondary ion mass spectrometry and X‐ray photoelectron spectroscopy, the authors confirm a probable "free phosphorus oxidation" reaction with particular results within the phosphosilicate glass. To unlock the fundamental mechanisms during POCl3 diffusion, the authors further present an advanced qualitative model with sketched schematics, which consistently explains results in the literature as well.